Validation of the Malay version of the smoking cessation quality of life (SCQoL) questionnaire / Muhammad Hafizul Shafiq Zainun - Zainun, Muhammad Hafizul Shafiq (2019)
The task of developing a new questionnaire or translating an existing questionnaire into a different language might be overwhelming. The greatest challenge perhaps is to come up with a questionnaire that is psychometrically sound, and is efficient and effective for use in research and clinical settings. (A Terkawi et, al., 2017) Although using an existing questionnaire will save time and resources, Boynton (2004) a questionnaire that measures the construct of interest may not be readily available, or the published questionnaire is not available in the language required for the targeted respondents. To date, there is no published studies on assessment tools to evaluate the effectiveness of smoking cessation programs on quality of life in Malay language. Thus, the validation of the Malays version of Smoking Cessation Quality of Life is important to ensure it can carry out its function and roles. This research aim is to test the reliability of Malay version of the Smoking Cessation Quality of Life (SCQoL) questionnaire and to determine the validity of Malay version of the Smoking Cessation Quality of Life (SCQoL) questionnaire. This research is based on data obtained from survey questionnaire that include the participation of smokers (n=30) and health-care professionals (n=10). The data was analysed to evaluate and determine the internal consistency reliability and the validity of the Malay version of Smoking Cessation Quality of Life. The results of the study suggested that the Malay version of the Smoking Cessation Quality of Life (SCQoL) questionnaire demonstrate validity and reliability as an instrument to quantify changes in self-reported functioning and well-being It is hope that the study can contribute to the improvement of smoking cessation and quality of life for smokers in Malaysia.